Tailings facility disclosures reveal stability risks - Franks, Daniel M.; Stringer, Martin; Torres-Cruz, Luis A.; Baker, Elaine; Valenta, Rick; Thygesen, Kristina; Matthews, Adam; Howchin, John; Barrie, Stephen (Scientific reports, 2021)
Tailings facility failures represent a significant risk to the environment and communities globally, but until now little data was available on the global distribution of risks and characteristics of facilities to ensure proper governance. We conducted a survey and compiled a database with information on tailings facilities disclosed by extractive companies at the request of institutional investors. Despite limitations in the data, this information disclosure request represents the most comprehensive survey of tailings facilities ever undertaken. The compiled dataset includes 1743 tailings facilities and provides insights into a range of topics including construction method, stability, consequence of failure, stored volume, and the rate of uptake of alternative technologies to dewater tailings and reduce geotechnical risk. Our analysis reveals that 10 per cent of tailings facilities reported notable stability concerns or failure to be confirmed or certified as stable at some point in their history, with distinct trends according to construction method, governance, age, height, volume and seismic hazard. Controversy has surrounded the safety of tailings facilities, most notably upstream facilities, for many years but in the absence of definitive empirical data differentiating the risks of different facility types, upstream facilities have continued to be used widely by the industry and a consensus has emerged that upstream facilities can theoretically be built safely under the right circumstances. Our findings reveal that in practice active upstream facilities report a higher incidence of stability issues (18.3%) than other facility types, and that this elevated risk persists even when these facilities are built in high governance settings. In-pit/natural landform and dry-stack facilities report lower incidence of stability issues, though the rate of stability issues is significant by engineering standards (> 2 per cent) across all construction methods, highlighting the universal importance of careful facility management and governance. The insights reported here can assist the global governance of tailings facility stability risks.